HUBUNGAN JARAK RUMAH DAN WAKTU TEMPUH DENGAN PEMANFAATAN PELAYANAN KESEHATAN SELAMA PANDEMI - Annisa Fatma Zafasia; Hellena Deli; Arneliwati Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
The pandemic causes a decrease in visits and utilization of health services and distance and travel time are one of the important factors in the utilization of health services. The purpose of this study was to determine the relationship between home distance and travel time with the use of health services during the pandemic. This study used a descriptive correlation research design with a cross sectional approach. The sample in this study were 73 families based on inclusion criteria determined by purposive sampling technique. The measuring instrument used is a questionnaire. The results of the analysis showed that the majority of respondents with close home distances and utilizing health services were 36 respondents (49.3%) and fast travel time and took advantage of health services as many as 35 respondents (47.9%), while respondents who have a long travel time and do not use health services are 3 respondents (4.1%). The analysis of the chi square test between the variable distance from home to the utilization of health services during the pandemic, obtained value = 0.059 with = 0.05 and using the chi square test between the variables of travel time on the utilization of health services during the pandemic, obtained value = 0.836 with = 0.05. The results Ho failed to be rejected, there was no relationship between home distance and travel time on the utilization of health services during the pandemic.Keywords: the utilization, health services, pandemic, home distance, travel time